Gaining insights into pet owner understanding/lived experience of canine chronic kidney disease using survey and social media data - Tarrant, Georgina; Boyden, Luke; Rai, Taranpreet; Wright, Andrea; Cook, Alasdair J. C.; Wells, Kevin (Frontiers in Veterinary Science, 2025)
IntroductionChronic kidney disease (CKD) is a common and progressive condition in dogs characterized by irreversible damage to one or both kidneys over an extended period leading to gradual decline in kidney function. Early diagnosis is crucial to improve quality of life and increase survival through medical interventions.MethodsThis study investigated pet owner understanding of this condition using insights gained by comparing pet owner survey responses with bulk harvested social media discussions on canine CKD. We combined structured survey data (n = 132) with social media analysis spanning multiple platforms to understand owner perceptions of disease characteristics, clinical sign reporting, and pet owner experiences.ResultsBoth data sources highlighted increased urination and water consumption as primary pet owner concerns, with these clinical signs showing moderate positive correlation (Pearson correlation coefficient of r = 0.66). Although not explicitly investigated within the survey, social media data demonstrated pain as a significant concerning clinical sign and revealed the emotional toll of end-of-life care considerations. Further analysis also demonstrated significant associations between CKD diagnosis in dogs and both animal age (p < 0.001) and female gender (p = 0.006), while breed group and weight showed no significant correlations.DiscussionThe complementary nature of structured surveys and social media analysis provided richer understanding of pet owner experiences, understanding and management of CKD. This combined methodological approach offers a model for investigating other chronic conditions in veterinary medicine.